К вопросу о статусе дифтонгов преломления - Забулене, Лайма (Kalbotyra, 1985)
The phonetic and phonological homogeneity of OE long and short diphthongs can be discovered first of all from their identical graphic representation. It should be noted that the graphic parallelism not only between long and short diphthongs but also between long and short monophthongs speaks for our line of interpretation. The graphic evidence is not the only data which supports our approach. Delabilization of the second element of the short diphthong /æu/ followed the delabilization of the long /æu /. There was also a great similarity between the processes of monophthongization of both types of diphthongs at the end of OE period.Length in OE diphthongs calls for additional comment. OE diphthongs can be characterized as long and short purely from the functional point of view because their exact quantitative characteristics are beyond our ability to reconstruct them.